A late bloomer : ZPMC CEO Guan Tongxian - Yang, Baiyin; Gao, Ang; Chen, Lu; McFarlan, F. Warren (Franklin Warren) ([London] : SAGE, 2016)
In December 2009, Shanghai Zhenhua Heavy Industries (ZPMC) issued a press release that 76-year-old President Guan Tongxian had decided to resign due to his age, and his resignation had been accepted by the Board of Directors. A special shareholders' meeting was convened on Christmas Day and agreed to recruit a new president. This text examines Guan Tongxian's career.
Originally Published in: Yang, B., Gao, A., Chen, L., & McFarlan, F. W. (2013). A Late Bloomer: ZPMC CEO Guan Tongxian (revised 15/10/2013). Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Guan, Tongxian; Shanghai Zhenhua Heavy Industries (Firm); Organizational behavior -- Case studies; Creative ability in business -- Case studies; Leadership -- Case studies